2022
DOI: 10.3389/fphar.2022.1000254
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate suppresses corneal neovascularization by regulating lipid metabolism through PPARα signaling pathway

Abstract: Purpose: The purpose of this study was to explore the potential underlying mechanism of anti-vascular effects of peroxisome proliferator–activated receptor α (PPARα) agonist fenofibrate against corneal neovascularization (CNV) through the changes of lipid metabolism during CNV.Methods: A suture-induced CNV model was established and the clinical indications were evaluated from day 1 to day 7. Treatments of vehicle and fenofibrate were performed for 5 days after suture and the CNV areas were compared among the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The length and area of CNV gradually grew with the extension of the stimulation time. On Day 5, the corneal rate-limiting barrier and tear secretion may interfere with BMP4 eye drops, preventing them from completely inhibiting CNV [ 32 , 33 ]. Poloxamer, however, exhibited histocompatibility, slow release, and good adherence.…”
Section: Resultsmentioning
confidence: 99%
“…The length and area of CNV gradually grew with the extension of the stimulation time. On Day 5, the corneal rate-limiting barrier and tear secretion may interfere with BMP4 eye drops, preventing them from completely inhibiting CNV [ 32 , 33 ]. Poloxamer, however, exhibited histocompatibility, slow release, and good adherence.…”
Section: Resultsmentioning
confidence: 99%
“…Fenofibrate is a lipid-lowering drug, and several studies have found that fenofibrate has a tumor-inhibiting effect [ 34 , 35 ]. Recent studies have demonstrated that fenofibrate can inhibit corneal neovascularization by controlling important enzymes of lipid metabolism, including ACADM [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, aganirsen is an antisense oligonucleotide and, unlike other agents, has FDA orphan drug designation to prevent corneal graft rejection; current phase III study results have suggested a significant inhibition of keratitis-induced corneal NV [65]. Targeted immunotherapy is a rapidly developing field with additional targets and delivery methods being considered, including nanoplatforms, atorvastatin-loaded peptide amphiphiles, and fenofibrate targeting the PPARα signaling pathway [66 ▪ ,67,68 ▪ ].…”
Section: Medical Therapiesmentioning
confidence: 99%